POWERPOINT INTRACTIVE QUIZ AS A LEARNING MEDIA IN IMPROVING SCIENCE GENERIC ABILITY IN MATERIAL CLASSIFICATION TOPIC - Isnanik Isna; Jihan Roidah Affifah (Universitas Negeri Surabaya, 2023)
The development of natural science in following the pace of technology, especially in the 4.0 era, has a significant impact on learning. The application of science concepts in everyday life is important for students. This study aims to develop a Power point Interactive Quiz learning media that can help improve students' generic science skills. This development research was carried out with the research subject, namely the seventh grade students of SMP Darul Quran Singosari. Science topics used Basic competence 3.3 Classification of materials and their changes. The research model used is 4D. Data collection techniques through observation and filling out questionnaires for students, teachers, media experts, and material experts. The resulting data are qualitative and quantitative data. The results of media validation by experts showed a percentage of 92.73% (very valid), material feasibility validation showed a percentage of 86.67% (valid), and the validity of the concept was 100% (very valid). The results of the practicality test by science subject teachers showed a percentage of 100% (very valid) and the results of the readability test by students showed a percentage of 91.89% (very valid). The effectiveness test is in the form of pretest and posttest t-test scores with results indicating that there are differences in the results of pretest and posttest scores. So based on some of the test results, the Power point Interactive Quiz learning media is feasible and effective to be applied in learning and can improve science generic skills.